Dangdut Music as a Realization of Indonesian Cultural Diplomacy and Social Relations Between Countries - Mochamad akmal (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
Music is a means of cultural diplomacy that has drawn considerable scholarly attention worldwide. This study describes the Indonesian government's efforts to strengthen cultural diplomacy at the international level through dangdut music, an effort aided by developments in the digital era, particularly television programming and pan-Asian sporting events. Dangdut Academy Asia and the 2018 Asian Games are treated here as two of the principal vehicles through which dangdut has been promoted on the international stage, particularly within Asia. The study draws on theories of popular culture and cultural diplomacy to explain how dangdut music, packaged for television, can shape public life in a constructive way.